Encouraging the development of children's oral communicative competences through play - Castrillón Olga Lucía (Universidad Nacional de Colombia, 2003)
When children start to learn a foreign language they already have some communicative competence in their mother tongue. Thus a classroom research project was carried out in order to study the development of children¿s competence in communicating in other languages. The main theme explored was if it was possible to help kids acquire and develop their competence in the new code through the use of play activities. The concepts related to competences, play and some children's characteristics when learning a second language will be presented in this article. Also, the results of the implementation of play activities in the classroom as well as some pedagogical implications will be analyzed as a means to promote improvement in the foreign language teaching-learning process. Key words: English-Primary School, Children Second Language Acquisition, Learning Ability in Children-Research, Educational Games-Teaching-Research Inglés-Escuela Primaria, Adquisición de Segundo Lenguaje en Niños, Aptitud de Aprendizaje en niños-Investigación, Cuando los niños empiezan el aprendizaje de una lengua extranjera ya poseen alguna competencia comunicativa en su lengua materna. De lo que se trata, por tanto en este proyecto de investigación en el aula es de promover esta competencia para comunicarse en otras lenguas. El propósito fundamental de esta investigación fue explorar si era posible ayudar a los estudiantes a adquirir y desarrollar su competencia en este nuevo código, mediante la implementación de actividades lúdicas. En este artículo se presentaran los conceptos de competencias, lúdica y algunas de las características de los niños en el aprendizaje de una segunda lengua. También se presentaran los resultados que surgieron a partir de la implementación de las actividades lúdicas y se mencionaran algunas implicaciones pedagógicas que promueven el mejoramiento del proceso de enseñanza-aprendizaje de una lengua extranjera.